An investigation into the control of audio streaming across networks having diverse quality of service mechanisms - Foulkes, Philip James (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
The transmission of realtime audio data across digital networks is subject to strict quality of service requirements. These networks need to be able to guarantee network resources (e.g., bandwidth), ensure timely and deterministic data delivery, and provide time synchronisation mechanisms to ensure successful transmission of this data. Two open standards-based networking technologies, namely IEEE 1394 and the recently standardised Ethernet AVB, provide distinct methods for achieving these goals. Audio devices that are compatible with IEEE 1394 networks exist, and audio devices that are compatible with Ethernet AVB networks are starting to come onto the market. There is a need for mechanisms to provide compatibility between the audio devices that reside on these disparate networks such that existing IEEE 1394 audio devices are able to communicate with Ethernet AVB audio devices, and vice versa. The audio devices that reside on these networks may be remotely controlled by a diverse set of incompatible command and control protocols. It is desirable to have a common network-neutral method of control over the various parameters of the devices that reside on these networks. As part of this study, two Ethernet AVB systems were developed. One system acts as an Ethernet AVB audio endpoint device and another system acts as an audio gateway between IEEE 1394 and Ethernet AVB networks. These systems, along with existing IEEE 1394 audio devices, were used to demonstrate the ability to transfer audio data between the networking technologies. Each of the devices is remotely controllable via a network neutral command and control protocol, XFN. The IEEE 1394 and Ethernet AVB devices are used to demonstrate the use of the XFN protocol to allow for network neutral connection management to take place between IEEE 1394 and Ethernet AVB networks. User control over these diverse devices is achieved via the use of a graphical patchbay application, which aims to provide a consistent user interface to a diverse range of devices.
Keywords: Streaming audio -- Testing; Data transmission systems -- Testing; Computer networks -- Management; Computer networks -- Evaluation; Computer network protocols -- Standards